Spread spectrum in mobile communication - Berg, Olav; Berg, Terv; Haavik, Svein; Hjelmstad, Jens; Skaug, Reidar (Institution of Electrical Engineers, 1998)
Mobile communication is one of the most important applications in the tele-communications and IT field. Developments in technology are enabling the design of advanced mobile radio networks linking information processing and data routing, with the radio segment sandwiched between layers of digital signal processors. Spread spectrum technology adapts radio communication to computational data information processing networks. This book presents the concepts of modern mobile communication and discusses the user requirements and operational environment which influence mobile systems design. Its focus is on the mobility issues for a decentralised network topology and the effects of spread spectrum modulation on radios used in packet-switched networks. Connecting radio terminals using packet switching gives a highly flexible and efficient solution for mobile users, and the book gives considerable space to discussing packet switching in radio networks, protocols and routing strategies. Providing vital information for all those in the mobile systems field, the book is supported by detailed case study information to illustrate the practical issues involved in implementing the technology.